Sovereign entrepreneurs : Cherokee small-business owners and the making of economic sovereignty - Lewis, Courtney (Critical indigeneities., 2019)
"[A] study of small businesses and small business owners who are members of the Eastern Band of Cherokee Indians (EBCI). The EBCI has an especially long history of incorporated, citizen-owned businesses located on their reservation. Many people stop with casinos or natural-resource intensive enterprise when they think of Indigenous-owned businesses, but on Qualla Boundary today, Indigenous entrepreneurship and economic independence extends to art galleries, restaurants, a bookstore, a funeral parlor, and more. Lewis's fieldwork followed these businesses before and after the Great Recession, and against the backdrop of a rapidly expanding Cherokee-owned casino. From this source base, Lewis reveals how these EBCI businesses have contributed to an economic sovereignty that empowers and sustains their nation both culturally and politically. This is a generative concept that helps to define what a distinctly Indigenous form of entrepreneurship looks like"--